Performance indicators that discriminate winning and losing in the knockout stages of the 2011 Rugby World Cup - Bishop, L.; Barnes, A. (International Journal of Performance Analysis in Sport, 2013)
The identification of performance indicators critical for success will allow the development of effective tactical approaches suited to the modern game. The aim of this study was to investigate the performance indicators that discriminate winning and losing teams in the knockout stages of the 2011 Rugby World Cup. Winning and losing teams from the eight knockout matches of the 2011 Rugby World Cup were compared based on several performance indicators previously associated with match success. A Wilcoxon test revealed statistical differences between only two performance indicators with winning teams conceding a higher percentage of their penalties between 50m and the opposition 22m than losing teams (P = 0.036) and winning teams kicking the ball out of hand more than losing teams (P = 0.040). Trends were noted in other indicators which supported the notion that winning teams adopted a more territory based strategy rather than a possession based approach to the game. Discipline in reducing the penalty count when defending in your own half was also found to be key in minimising potential scoring opportunities for the attacking team. At the 2011 Rugby World cup, a territory based approach appeared to be the most effective strategy for game success.